Zagadnienie obiektywnego ładu systemów wiedzy w koncepcjach Floriana Znanieckiego i Karla Popper - Ziółkowski, Marek (Wydział Prawa i Administracji UAM, 1982)
The article opens with an indication that the conception of cultural systems of Florian Znaniecki is the counterpart of the notion of World 3 of Karl Popper, although the first was formulated much earlier and in more general categories. Both conceptions assume the existence of objective systems of human knowledge which are human creations gradually reaching autonomy, being possessed of inner order and a defined logic of development. The author attempts at interpreting that idea on the grounds of a conception of human knowledge which implies that any knowledge is nothing more than convictions of one or many individuals. The systems of objective knowledge are interpreted as a sphere of intermediate, stable communication understood in the potential aspect of it. This can influence their ordering, interrelation of elements as well as the possibility of introducing supplementary consequences, not perceived initially, and putting forward new problems. Separate individuals who are the only subjects of knowledge are independently of them involved in the social relations with other individuals and groups, having no effect whatsoever on their convictions and they are also put under the influence of stable media transferring the ordered systems of knowledge which can also be supplemented.
The question of Objective Order of the Systems of Knowledge in the Conceptions of Znaniecki and Popper